Acute respiratory failure and inflammatory response after out-of-hospital cardiac arrest: results of the Post-Cardiac Arrest Syndrome (PCAS) pilot study. Issue 4 (November 2020) - Czerwińska-Jelonkiewicz, Katarzyna; Grand, Johannes; Tavazzi, Guido; Sans-Rosello, Jordi; Wood, Alice; Oleksiak, Anna; Buszman, Piotr; Krysiński, Mateusz; Sionis, Alessandro; Hassager, Christian; Stępińska, Janina
Background: Although the lungs are potentially highly susceptible to post-cardiac arrest syndrome injury, the issue of acute respiratory failure after out-of-hospital cardiac arrest has not been investigated. The objectives of this analysis were to determine the prevalence of acute respiratory failure after out-of-hospital cardiac arrest, its association with post-cardiac arrest syndrome inflammatory response and to clarify its importance for early mortality. Methods: The Post-Cardiac Arrest Syndrome (PCAS) pilot study was a prospective, observational, six-centre project (Poland 2, Denmark 1, Spain 1, Italy 1, UK 1), studying patients resuscitated after out-of-hospital cardiac arrest of cardiac origin. Primary outcomes were: (a) the profile of organ failure within the first 72 hours after out-of-hospital cardiac arrest; (b) in-hospital and short-term mortality, up to 30 days of follow-up. Respiratory failure was defined using a modified version of the Berlin acute respiratory distress syndrome definition. Inflammatory response was defined using leukocytes (white blood cells), platelet count and C-reactive protein concentration. All parameters were assessed every 24 hours, from admission until 72 hours of stay. Results: Overall, 148 patients (age 62.9±15.27 years; 27.7% women) were included. Acute respiratory failure was noted in between 50 (33.8%) and 75 (50.7%) patients over the first 72 hours. In-hospital and short-term mortality was 68 (46.9%) and 72 (48.6%), respectively. Inflammation was significantly associated with the risk of acute respiratory failure, with the highest cumulative odds ratio of 748 at 72 hours (C-reactive protein 1.035 (1.001–1.070); 0.043, white blood cells 1.086 (1.039–1.136); 0.001, platelets 1.004 (1.001–1.007); <0.005). Early acute respiratory failure was related to in-hospital mortality (3.172, 95% confidence interval 1.496–6.725; 0.002) and to short-term mortality (3.335 (1.815–6.129); 0.0001). Conclusions: An inflammatory response is significantly associated with acute respiratory failure early after out-of-hospital cardiac arrest. Acute respiratory failure is associated with a worse early prognosis after out-of-hospital cardiac arrest.